Literature review of the key variables of the co-creation process in higher education institutions. - Ribes Giner, Gabriela (2017)
Value co-creation has been broadly developed as a new paradigm in management innovation. It allows companies and customers to create value through interaction. However, it has not been examined in depth in Higher Education contexts as a type of service industry. The present paper clarifies value co-creation in Higher Education Institutions, analysing the relationships between key factors affecting it: communicative participation, trust, satisfaction and loyalty. A literature review was conducted, resulting in 84 relevant papers dealing with the studied topic. The study was focused on the micro level, and, specifically, it analyses the relation between students and Higher Education institutions as main actors of value co-creation within this context. This perspective corresponds to the new trends in university teaching-learning framework, where professors are no longer the heart of the process, to become just a part of it. This shift makes students the backbone of the value co-creation process. This study provides, among other things, a conceptual framework to endorse further works on value co-creation in Higher Education institutions.